Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/gox.0000000000003042
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells in Head and Neck Cutaneous Squamous Cell Carcinoma Express Cathepsins

Abstract: Background: Cancer stem cell (CSC) subpopulations within moderately differentiated head and neck cutaneous squamous cell carcinoma (MDHNcSCC) express the components of the renin–angiotensin system (RAS). This study investigated the expression of cathepsins B, D, and G, which constitute bypass loops of the RAS, by CSCs in MDHNcSCC. Methods: Immunohistochemical staining was performed on MDHNcSCC tissue samples from 15 patients to determine the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In these studies, trans-differentiation processes that take place during tissue repair, tumorigenesis and organogenesis have been widely explored through three-dimensional (3D) tissue-derived spheroid systems. In contrast with 2D structures, 3D systems mimic patho-physiological processes, allowing cell–cell, cell-matrix and cross-talk interactions [ 91 , 92 , 93 ]. Studies on 3D systems have shown that trans-differentiation processes such as EMT and MET, both of which are involved in regenerative process, can balance stemness of tumoral and non-tumoral cells and promote the differentiation of specific cell phenotypes [ 94 , 95 ].…”
Section: Tissue Regeneration and Emtmentioning
confidence: 99%
“…In these studies, trans-differentiation processes that take place during tissue repair, tumorigenesis and organogenesis have been widely explored through three-dimensional (3D) tissue-derived spheroid systems. In contrast with 2D structures, 3D systems mimic patho-physiological processes, allowing cell–cell, cell-matrix and cross-talk interactions [ 91 , 92 , 93 ]. Studies on 3D systems have shown that trans-differentiation processes such as EMT and MET, both of which are involved in regenerative process, can balance stemness of tumoral and non-tumoral cells and promote the differentiation of specific cell phenotypes [ 94 , 95 ].…”
Section: Tissue Regeneration and Emtmentioning
confidence: 99%
“…We have previously demonstrated expression of cathepsins B, and D by CSCs in a number of cancer types ( 34 36 ) including primary HNcSCC ( 37 ). In this study, immunofluorescence staining demonstrated localization of cathepsins B and D to the CSCs within both the TNs and the PTS, and cathepsin G on the phenotypic mast cells within the PTS, similar to OTSCC ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsins also prevent cell death through modulation of the lysosomal apoptotic pathways and promote cancer cell invasion through upregulation of cell adhesion and migration ( 30 ). Cathepsins B and D are expressed by CSCs in glioblastoma ( 34 ), oral tongue SCC (OTSCC) ( 35 ), metastatic colon adenocarcinoma to the liver ( 36 ) and primary HNcSCC ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…These alternative signaling pathways enable the RAS to evade single-point inhibitions by traditional RAS inhibitors (RASIs) [ 120 ]. Expression of cathepsins B, D and G has been demonstrated in numerous cancer types including glioblastoma [ 121 ], head and neck SCC [ 122 , 123 ], malignant melanoma [ 124 ], oral tongue SCC [ 125 ], and liver metastasis from colorectal cancer [ 126 ]. Similar to the expression of components of the RAS within these cancer types, cathepsins B and D are expressed on the phenotypic CSC population, while cathepsin G is expressed by phenotypic mast cells.…”
Section: The Tumor Microenvironment and Its Role In Tumor Recurrence ...mentioning
confidence: 99%